Comparison of COVID-19 and seasonal HCoV pathologies and transfer to endemic state - Antia, Rustom (Henry Stewart Talks, 2021)
Approach to modelling future of COVID-19 using historical seasonal Coronavirus data, Endemic season Coronaviruses (HCoVs) in the population, Differences between immunological responses to SARS-CoV-2 versus seasonal HCoVs, Potential evolution of the COVID-19 pandemic, Transfer of COVID-19 to endemicity, Continued vigilance towards SARS-CoV-2 in the post-pandemic world